Radiologically and clinically diagnosed acute pulmonary oedema in critically ill patients: Prevalence, patient characteristics, treatments and outcomes - Khaled El-Khawas (2022)
Background: Acute pulmonary oedema is a life-threatening syndrome diagnosed based on radiological and clinical findings. However, to our knowledge, no studies have investigated this syndrome in critically ill patients. Objective: To describe the prevalence of radiologically and clinically diagnosed pulmonary oedema (RCDPO) in critically ill patients, characteristics of diagnosed patients, and treatments and outcomes in this patient population. Methods: We conducted a retrospective study using natural language processing to identify all radiological reports of pulmonary oedema among patients who had been admitted to single tertiary intensive care unit (ICU) over a 1-year period (January 2015 to January 2016). We reviewed clinical data, discharge diagnosis, treatment and outcomes for such patients, and used multivariable logistic regression analysis to identify the association of RCDPO with various outcomes. Results: Out of 2001 ICU patients, we identified 238 patients (11.9%) with RCDPO. Patients with RCDPO were more acutely ill, had more chronic liver disease and had more chronic renal failure than critically ill patients who did not have RCDPO. They were typically admitted with acute cardiovascular disease; were more likely to receive invasive mechanical ventilation and continuous renal replacement therapy; had longer duration of ICU and hospital stay; were more likely to die in hospital; and, if discharged alive, were more likely to be admitted to a chronic care facility. In total, 46 RCDPO patients (19.3%) died in hospital. On multivariable analysis, only age and continuous renal replacement therapy were independently associated with mortality. In contrast, invasive mechanical ventilation was associated with a 2.5 times greater odds of radiological resolution. Conclusion: RCDPO affected about one in eight ICU patients. Such patients were sicker and had more comorbidities. The presence of RCDPO was independently associated with higher risk of death. Invasive mechanical ventilation was the only intervention independently associated with greater odds of radiological resolution. Accordingly, we used the combination of radiological diagnosis and confirmatory clinical assessment to define the presence of pulmonary oedema in a cohort of critically ill patients admitted to the ICU of a tertiary institution over a 1-year period. In this cohort of critically ill patients, we aimed to describe the prevalence of RCDPO, patient characteristics, and treatments, risk factors and outcomes. In particular, we aimed to test the hypothesis that, compared with patients without RCDPO, those with pulmonary oedema would have a significantly greater mortality rate.